Absent mandate strategies and choices in Canadian elections - Clarke, Harold D. 1943-; Jenson, Jane 1946-; LeDuc, Lawrence; Pammett, Jon H. 1944- (University of Toronto Press, 2019)
"Absent Mandate develops the crucial concept of policy mandates, distinguishes them from other interpretations of election outcomes, and addresses the disconnect between election issues and government actions. Emphasizing Canadian federal elections between 1993 and 2015, the book examines the Chretien/Martin, Harper and Trudeau governments and the campaigns that brought them to power. Using data from the Canadian Election Studies and other major surveys, Absent Mandate documents the longstanding volatility in Canadian voting behaviour. This volatility reflects the flexibility of voters' partisan attachments, the salience of party leader images, and campaigns dominated by discussion of broad national problems and leaders rather than by coherent sets of policy proposals. The failure of elections to provide genuine policy mandates stimulates public discontent with the political process and widens the gap between the promise and the performance of Canadian democracy."--
Includes bibliographical references and index.
Keywords: Kanada -- Parliament -- House of Commons; Geschichte 1993-2015; Wahl; Elections / Canada / History / 20th century; Elections / Canada / History / 21st century; Voting / Canada; Political participation / Canada; Élections / Canada / Histoire / 20e siècle; Élections / Canada / Histoire / 21e siècle; Vote / Canada; Participation politique / Canada